Silurian deformation in eastern Notre Dame Bay, Newfoundland - Lafrance, Bruno; Williams, Paul F. (Canadian Journal of Earth Sciences, 1992)
Eastern Notre Dame Bay, Newfoundland, is divided into five fault-bounded terranes. They are, from north to south, the Twillingate Terrane, the Chanceport Terrane, the New World Island Terrane, the Dildo Run Terrane, and the Port Albert Terrane. The New World Island Terrane is characterized by fault-repeated sequences of Middle Ordovician to Early Silurian turbiditic sandstones (Sansom Formation) and conglomerates (Goldson Formation). The Chanceport Terrane has a lower volcanic unit and an upper sedimentary unit consisting of red and green siltstones–shales overlain by turdiditic sandstones. This sequence is structurally overlain by a mafic and felsic volcanic unit.The clastic sedimentary rocks of the Chanceport, New World Island, and Port Albert terranes best record the Silurian deformation in the area. Silurian deformation is divided into two deformation events: an Early Silurian D 1 thrusting event and a Late Silurian D 2 dextral ductile faulting event. The Early Silurian Joey's Cove Mélange constrains the age of D 1 thrusting. Few small-scale fault ramps and intrafolial F 1 folds are associated with D 1 thrusting. Most penetrative deformation structures in eastern Notre Dame Bay formed during D 2 . Three fold generations (F 2 , F 3 , F 4 ), the regional cleavage (S 3 ), and tectonic mélanges are associated with D 2 dextral ductile faulting. D 2 structures overprint Early Silurian Goldson conglomerates, and are overprinted by Late Silurian to Early Devonian Loon Bay Suite intrusions. Devonian to Mesozoic brittle D 3 faults cut across the ductile regional structures.Silurian deformation in eastern Notre Dame Bay began during the closure of the Iapetus Ocean when the Chanceport, New World Island, and Port Albert terranes, and possibly the Twillingate and Dildo Run terranes, were thrust towards the south over the Gander Zone. D 2 dextral ductile faults formed to accommodate the nonorthogonal final closure of the Iapetus Ocean. The closure of the Iapetus Ocean in eastern Notre Dame Bay was oblique with a dextral ...